IMPLEMENTATION OF THE INTERNAL CONTROL SYSTEM ON THE EFFECTIVENESS OF ASSET MANAGEMENT AT THE UNIVERSITY OF NORTH SUMATRA WITH LEADERSHIP COMMITMENT AS A MODERATING VARIABLE - Syafina Fathlia Yasmin; Elisabet Siahaan; Isnen Fitri (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Asset management aims to ensure that assets are used optimally according to organisational needs, in order to increase efficiency and productivity. To ensure that assets are used optimally, it is necessary to implement an organisation's internal control system. This study aims to analyse the effect of the internal control system consisting of the control environment, risk assessment, control activities, information and communication, and monitoring on the effectiveness of asset management at the University of North Sumatra, with leadership commitment as a moderating variable. This research is motivated by the importance of asset management at Legal Entity State Universities (PTN-BH) such as USU which has autonomy in managing its assets, as well as findings of weaknesses in recording and competence of human resources managing assets. This research uses a quantitative approach with a survey method through distributing questionnaires to academic units and administrative units within USU. The results showed that all elements of the internal control system had a positive and significant effect on asset management. However, leadership commitment only plays a significant moderating role in the relationship between monitoring and asset management, while in other variable relationships it is not significant.